Heatwaves and a decrease in turbidity drive coral bleaching in Atlantic marginal equatorial reefs - Lucas, Caroline Costa; Teixeira, Carlos Eduardo Peres; Braga, Marcus Davis Andrade; Júnior, Francisco Carlos; Paiva, Sandra Vieira; Gurgel, Anne Larisse; Rossi, Sergio; Soares, Marcelo Oliveira (Frontiers in Marine Science, 2023)
Tropical reefs can occur naturally under suboptimal environmental conditions, where few reef-building corals thrive. These unique reefs are especially important for understanding resistance to global warming, but they are understudied. We studied a coral bleaching event that occurred in turbid reefs (~ 19 m deep) in the equatorial southwestern Atlantic. Mass bleaching was observed in 91% of the Siderastrea stellata colonies in 2020, whereas only 7.7% of the colonies were bleached in 2019 and 10.9% in 2022. The year 2020 had the highest heat stress recorded in this century in this region according to the degree of heating weeks such as 17.6°C-week. In the first semester of 2020, the region also underwent three marine heatwaves (MHWs) above the average temperatures (1.3, 1.5, and 2.0°C). The lowest turbidity and wind speed matched long-lasting, repeated, and severe MHWs. These reef-building corals are dominant under moderate turbid waters and high sea temperature (26–29°C), however they are near the maximum tolerance limit. In this regard, these low-latitude reefs are warming twice as fast (0.2°C/decade) as other regions (e.g., Abrolhos and Coral Coast) (0.1 to 0.13°C/decade) in the South America reef system demonstrating that they cannot be considered climate-change refugia. These results suggest that even turbid marginal reefs and tolerant corals are highly susceptible to mass bleaching, especially when heatwaves and a decrease in turbidity occur simultaneously.